PERANAN PEMERINTAH DAERAH DALAM PEMBERDAYAAN KELOMPOK TANI UNTUK MENINGKATKAN HASIL PANEN PADI - Soetarto Soetarto; Besti Rohana Simbolon; Sabali Zebua (JURNAL GOVERNANCE OPINION, 2019)
One of the community empowerments that is currently being carried out by the Regional Government at Kelurahan Mabar Hilir is the Rice Farmer Group Program. The research method used is Qualitative method. The Data Collection Techniques used in this study are interviews, documentation and observation. Types and sources of data used in this study are Primary Data and Secondary Data. Based on the results of research that has been described on the Role of Local Government in empowering farming communities to increase rice yields, explains that the government has collaborated with the Department of Agriculture and Maritime Affairs in terms of providing agricultural facilities such as providing plowing machines (Jetor), water pumping machines, subsidized fertilizers, seeds, rice threshing machines by partnering with agricultural field practice (PPL) to provide counseling to farmers. Community empowerment of farmer groups in the village of Mabar Hilir, Medan Deli sub-district has been implemented and has been felt by the farming community well, but in addition there are still obstacles such as agricultural land that is increasingly decreasing, agricultural land ownership and irrigation are not available. The role of the Regional Government in empowering the peasant community is to further strive for the interests of the community in the form of policies so that the community does not experience overwhelmed to work on programs from the Regional Government, namely the farmer group program.